Impact of Sowing Date Induced Temperature and Management Practices on Development Events and Yield of Mustard (Bangladesh Agronomy Journal, 2016)
The experiment was conducted at the research field of the Agronomy Division, Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur, during rabi season of 2014-2015 to find out the relationship between different development events of mustard crop and sowing dates induced temperature as well as to minimize the yield reduction of the crop by adopting appropriate management practices. The mustard var. BARI Sarisha-15 was sown on 06, 25 November and 14 December 2014. Crop accumulated lower growing degree days (GDD) i.e., 72.15, 521.10 and 1070 to 1154 °C were observed for the events of emergence, 50 % flowering and maturity on 14 December sowing. Late sown plants took minimum time from flowering to maturity (36 days) due to increased temperature and high variability in both maximum and minimum temperature. The highest seed yield (1569 kg ha-1) was recorded from 06 November sowing with high management practices while the lowest seed yield (435 kg ha-1) from 14 December sowing with low management practices. At high management practices the crop yielded 1183 kg ha-1 at 14 December sowing. Yield reduction at late sowing condition was reduced to some extent with high management practices. The seed yield reductions at 14 December sowing as compared to high management practices at 06 November sowing were 72, 43 and 25% under low, medium and high management, respectively.Bangladesh Agron. J. 2015, 18(2): 45-52